Cerebrovascular function response to prolonged sitting combined with a high‐glycemic index meal: A double‐blind, randomized cross‐over trial. (28th April 2021) - Burnet, Kathryn; Blackwell, Jade; Kelsch, Elizabeth; Hanson, Erik D.; Stone, Keeron; Fryer, Simon; Credeur, Daniel; Palta, Priya; Stoner, Lee
Abstract: Acute prolonged sitting leads to cerebrovascular disruptions. However, it is unclear how prolonged sitting interacts with other common behaviors, including high‐ (HGI) and low‐glycemic index (LGI) meals. Using a double‐blind randomized cross‐over design, this study evaluated the effects of prolonged (3 hr) sitting, with a high‐ (HGI; GI: 100) or low‐glycemic index (LGI; GI: 19) meal on total brain blood flow (QBrain ) and executive function. Eighteen young, healthy, active participants (22.6 [3.1] y, 33% F, 24.3 [3.7] kg/m 2 ) sat for 3 hr after consuming an HGI or LGI meal. Using Doppler ultrasound to measure internal carotid (ICA) and vertebral (VA) artery blood flow, QBrain was calculated: (ICA blood flow + VA blood flow) × 2. Executive function was assessed using the Stroop Test and Trail Making Test—Part B. Brain fog was measured using a modified Borg Category Scale with Ratio properties (CR10). Following 3 hr of sitting, there was a significant decrease in QBrain with time ( p = .001, ES = −0.26), though there were nonsignificant interaction ( p = .216) and condition effects ( p = .174). Brain fog increased ( p = .024, ES = 0.27) and Stroop reaction time worsened with time ( p = .001, ES: −0.40), though there were nonsignificant condition effects for brain fog ( p = .612) and the Stroop test ( p = .445). There was a nonsignificant condition effect ( p = .729) for the Trail Making Test—Part B, but completion time improved with time ( p = .001, ES = −0.40). In conclusion, 3 hr of prolonged sitting decreases QBrain and executive function independent of glycemic index in young, healthy adults. Abstract : Acute prolonged sitting leads to cerebrovascular disruptions. However, it is unclear how prolonged sitting interacts with other common behaviors, including the consumption of high and low glycemic index meals. We provide evidence that prolonged sitting (3 hr) decreases total brain blood flow regardless of the glycemic index of the meal, while maintaining oxygen delivery in young, healthy adults.